Cultural Identity and Its Impact To Students’ English Proficiency; A Case Study - Tatu Zakiyatun Nufus (Universitas Cokroaminoto Palopo, 2022)
cultural identity is considered as collective, shared history among individuals affiliated by race that is fixed or stable and identity understood as unstable, metamorphic, and even contradictory an identity marked by multiple points of similarities as well as differences (Hall, 2003). This article aimed to describe the cultural identity that impact English proficiency and find out the factors that impact student’s English proficiency, this study was done at private school of Al-Mansyuriyah Tangerang and four students are used as participant to give data, the study used observation, questionnaire and interview. In this case, the researcher identified that cultural identity affect students’ English proficiency, especially in speaking which includes spelling, pronunciation, intonation, and structure. And based on the observation and interview that have been done by the researcher, she found that there are many factors that impact English proficiency at Al-Mansyuriyah such as dialect, pronunciation, heritage language and language structure, based on this finding, the researcher suggest that the teacher is need to teach English language in whole skills using a good strategy in conveying the language to student including the cultural identity of students that can raise students’ awareness of cultural identity and English proficiency